Consequences of runaway and thrownaway experiences for sexual minority health during the transition to adulthood. Issue 2 (3rd April 2017) - Pearson, Jennifer; Thrane, Lisa; Wilkinson, Lindsey
ABSTRACT: Sexual minority youth are more likely to run away from home or experience homelessness, leaving them at increased risk of victimization and negative health outcomes. In this study, the authors use a developmental perspective that considers both vulnerable beginnings in families and the risky trajectories that follow to explore the connections between running away or being thrown out by parents and sexual minority women's and men's health in adulthood. Using four waves of data from the National Longitudinal Study of Adolescent to Adult Health (Add Health), the authors consider multiple dimensions of health and several potential intervening mechanisms. Findings suggest that runaway and thrownaway experiences have persistent negative effects on health into adulthood, in part because of their association with sexual victimization, educational attainment, and relationships with parents. Sexual minority men who have been thrown out by parents report a greater likelihood of suicidal ideation, smoking, and substance use into adulthood. Sexual minority women with runaway experiences have poorer health and increased depressive symptoms, while women with thrownaway experiences engage in more health risk behaviors. Sexual victimization stands out as a key mechanism for sexual minority women's health, as more than half of these young women report experiences of sexual victimization.